Night conversations with Cardinal Martini the relevance of the Church for tomorrow - Martini, Carlo Maria, 1927-2012.; Sporschill, Georg, 1946-; Henry, Lorna (Mahwah, NJ : Paulist Press, 2012)
"Carol M. Martini was cardinal of the largest diocese in the world, a scholar, and one of the most renowned men of the church. Georg Sporschill has worked in prisons and lived with drug-addicted street children in Romania and Moldavia. The two Jesuits met in Jerusalem and became firends: two worlds, one faith--and a passionate search for ways in which the message of Jesus of Nazareth can still be effective for tomorrow. In a series of conversations they ask what faith can mean for life, what future young people have in the church, and what must be changed so that Crhistianity itself has a future. The questions from young people are the catalyst for deep thought. Is the future only dark? Where are the rays of light on the horizon? What would Jesus say today?" - back cover
What sustains life? -- Courage to decide -- Making friehnds -- Being close to God -- Learning to love -- For an open chruch -- fighting against injustice.
Description based on print version record.
Keywords: Catholic Church -- Doctrines; Youth -- Religious life; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books